Utilisation of biomass wastes based activated carbon supported heterogeneous acid catalyst for biodiesel production - Tang, Zo Ee; Lim, Steven; Pang, Yean Ling; Shuit, Siew Hoong; Ong, Hwai Chyuan (Elsevier, 2020)
This study evaluated the utilisation of biomass wastes as catalyst supports by comparing the catalytic performance of papaya seed, empty fruit bunch (EFB) and corncob biomass waste derived carbon based acid catalysts applied for biodiesel production through esterification reaction of palm fatty acid distillate (PFAD) and methanol. Arylation of 4-benzenediazonium sulfonate synthesis method was able to sulfonate the catalyst support efficiently. The activated carbon (AC) synthesised possessed high porosity with surface area ranged between 639.68 and 972.66 m2/g. The effect of catalyst synthesising condition including carbonisation temperature (600–1000 °C), sulfonation time (0.5–2.5 h) and sulfanilic acid to AC weight ratio (3:1–13:1) towards the FAME yield and free fatty acid (FFA) conversion were evaluated. At the optimum catalyst synthesis conditions, corncob waste derived sulfonated AC catalyst exhibited the highest FAME yield and FFA conversion of 72.09% and 93.49%, respectively. Reusability study showed that corncob waste derived sulfonated AC catalyst was able to achieve relatively high FAME yield at the first two reaction cycles. The esterification reaction followed the irreversible pseudo-homogeneous reaction model. The high catalytic efficiency of the catalyst had shown its high potential to fit into the cost-effective and sustainable framework for biodiesel production. © 2020 Elsevier Ltd